2005
DOI: 10.1590/s0100-204x2005000500006
|View full text |Cite
|
Sign up to set email alerts
|

Macropropagation and micropropagation of Ziziphus spina-christi

Abstract: -Christ's thorn (Ziziphus spina-christi (L.) Desf.) is a cross-pollinated plant with a wide range of genetic variability in nature and, for this reason, vegetative propagation assumes importance for improvement programs. The objective of this work was to evaluate cutting, T budding and tissue culture methods for this species. Shoots of 22-25 cm length were treated by two culture media and three shoot diameters for cutting trial. The T budding treatments consisted of three and five collection dates in spring an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…In our experiments, treatments with calcium hypochlorite [Ca(ClO) 2 ] were satisfactory for sterilization ( Figure 2). Assareh and Sardabi (2005) reported that among treatments with Ca(ClO) 2 , NaOCl and HgCl 2 for tissue culture explants sterilization of Ziziphus spina-christi (L.)Desf., Ca(ClO) 2 in concentration of 5% and duration of 20 minutes was the most efficient. Comparing the effect of HgCl 2 and NaOCl in our experiment, NaOCl was found to be better, with more survived explants (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…In our experiments, treatments with calcium hypochlorite [Ca(ClO) 2 ] were satisfactory for sterilization ( Figure 2). Assareh and Sardabi (2005) reported that among treatments with Ca(ClO) 2 , NaOCl and HgCl 2 for tissue culture explants sterilization of Ziziphus spina-christi (L.)Desf., Ca(ClO) 2 in concentration of 5% and duration of 20 minutes was the most efficient. Comparing the effect of HgCl 2 and NaOCl in our experiment, NaOCl was found to be better, with more survived explants (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Since Ziziphus spina [christti] is a cross-pollinated plant, a wide range of genetic variability exists in the nature. Vegetative propagation, particularly in vitro propagation, assumes importance for mass and clonal propagation (Assareh and Sardabi 2005). Since seeds of Z. spina [christti] require scarification treatments to germinate (Moustafa et al 1998), vegetative propagation plays a significant role in its improvement in breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the collecting time of buds and grafts might have negatively influenced the experiment results. Assareh and Sardabi (2005), for instance, obtained better results on the grafting of Ziziphus spina-christi (L.) Desf. performed in autumn than in spring.…”
Section: Graftingmentioning
confidence: 99%
“…Although there are studies that testify the importance of different aspects on the grafting success, such as the used method, rootstock and graft origin, rootstock age and environmental conditions (ASSAREH; SARDABI, 2005), the studied factors did not influence the evaluated variables. Furthermore, the collecting time of buds and grafts might have negatively influenced the experiment results.…”
Section: Graftingmentioning
confidence: 99%